A catecholaminergic sensory neuron phenotype in cranial derivatives of the neural crest: regulation by cell aggregation and nerve growth factor - Katz, DM (J Neurosci, 1991)
Tyrosine hydroxylase (TH) is transiently detectable in cells distributed throughout cranial sensory ganglia during early stages of gangliogenesis [embryonic day (E) 10.5-15.5]. Although TH cells appear in embryonic ganglia of both neural crest and placode origin, mature cranial sensory neurons that express catecholaminergic properties are restricted to placode derivatives. The mechanism(s) underlying the loss of TH expression in crest-derived sensory ganglia is unknown, and the present study was undertaken to define the temporal regulation of this phenotype. Our data indicate that transient TH cells belong to a large subset of primary sensory neurons that exhibit the capability to express TH throughout development. The lack of TH expression after E15.5 appears to be due to modulation of this catecholaminergic potential. The phenotype reappears, however, when E16.5 and older ganglia are dissociated in culture into single cells, suggesting that factors associated with cell aggregation modulate TH expression. In support of this hypothesis, sensory neurons grown at high cell density exhibit lower levels of TH expression than low-density cultures. The decrease in TH levels seen at high density was associated with changes in sensory neuron morphology that are characteristic of ganglion cell maturation in vivo; therefore, modulation of TH expression may be only one facet of a more general program of sensory neuron differentiation associated with cell aggregation in developing ganglia. In contrast to the effects of cell aggregation, treatment with NGF increased the proportion of TH cells in dissociate cultures of E14.5 and E16.5 cranial sensory ganglia. Our findings indicate that sensory transmitter phenotype may be modulated by multiple factors during gangliogenesis, including cellular interactions intrinsic to the developing ganglionic microenvironment.